Infrared images help to identify retinal emboli in hemodynamic retinal artery occlusion - Yu Chen; Hsiao-Fan Tung; Jiunn-Feng Hwang (Taiwan Journal of Ophthalmology, 2024)
To report a case of stroke with internal carotid artery (ICA) occlusion and retinal artery occlusion (RAO) with multiple emboli identified by infrared images. The patient presented with acute blurred vision and slurred speech since woke up in the morning. Carotid Doppler ultrasonography showed severe left ICA stenosis with the decreased flow. Computed tomography angiography demonstrated left ICA critical stenosis with compensatory flows from the right ICA. There was coexistent RAO with multiple emboli, silver-wiring, and segmentation of the retinal artery. More hyperreflective emboli were uncovered by infrared images of spectral-domain optical coherence tomography. Embolism may accompany with the compensatory flow for ICA occlusion. RAO patients should have thorough carotid evaluations, especially those with multiple retinal emboli.